Problem psihičnega nasilja med zaposlenimi v vzgojno-izobraževalnih institucijah - Pšunder, Mateja (Šolsko polje, 2012)
Psychological violence is a broader term in comparison to the term mobbing, which refers to the psychological violence that occurs specifically within the workplace. It is defined as unethical communication in the work environment caused by one or more people and is usually directed towards an individual or groups. The consequences of mobbing can be unpleasant for the victim, the institution and the whole society. Owing to the mission of educational institutions, the consequences of mobbing in their environment are even more complex and long-term. Pre-school and school teachers with their behaviour and relation to others in school or kindergarten cocreate a space where children acquire their social and emotional experience. In our research, the problem of psychological violence in educational institutions was given special attention. We have researched which psychologically violent behaviours are, according to interviewees, present amongst employees in educational institutions on different levels: in kindergarten, primary and secondary school. The research has confirmed that employees in educational institutions agree that various psychologically violent behaviours are present in educational institutions at all levels. Preschool, primary school and secondary school teachers most agree that the category of mobbing behaviour, meaning an attack on expression and communication, is indeed present in their institution. Amongst individual behaviours, the interviewees most commonly affirm that in their institution one can find reduced possibilities for expressing oneself and his/her opinion. The research has confirmed some differences regarding the presence of particular mobbing behaviours amongst employees in educational institutions on different levels.
Keywords: mobbing; vzgoja in izobraževanje; mobing; psychological violence; psihično nasilje; teacher as a model; učitelji; educational institutions; vzgojno-izobraževalne institucije; raziskave